THE ROLE OF CONSULATE GENERAL OF INDONESIA JOHOR BAHRU MALAYSIA IN ATTEMPTS TO ACCOMPLISH INDONESIAN LABOR PROBLEMS IN MALAYSIA - Ayu Lestari (HI 15 UMY 197, 2015)
*197 The research examine the role of Consulate General of Indonesia Johor Bahru in attemps to accomplish Indonesian labor problem in Malaysia. The aims of this research are to analyze and to describe the cause of violence against Indonesia labor still happen in Johor Bahru. This is qualitative research used by deductive methods. The research finding shows that the role of Consulate General of Indonesia Johor Bahru are coordinating with related parties and enabling the Bilateral Agreement, as the representative of the Republic of Indonesia that provides protection against labour workers abroad in accordance with laws, regulations and international customs,provide protection to migrant workers abroad, accordingby legislation, to provide guidance and supervision of a representative PPTKIS (perwakilan pelaksana penempatan TKI swasta) and labours who are placed abroad, supervision of the implementation of the placement and protection of migrant workers abroad carried out by the Representative of the Republic of Indonesia in the destination country.